Preparation method of heterostructure sodium electrode layered oxide positive electrode material

The sodium ions are embedded in the potassium ion layered oxide precursor by ion exchange method to form a P2/O3 heterostructure, which solves the problem of insufficient cyclic stability and rate performance of sodium-electric layered oxide positive electrode materials in the prior art, and achieves the effect of high energy density and fast charging and discharge.

CN119503887APending Publication Date: 2025-02-25CENT SOUTH UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411615259.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-13
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The prior art is difficult to improve the cyclic stability and rate performance of sodium-electric layered oxide cathode materials while maintaining high energy density.

Method used

The potassium ion layered oxide precursor is used to achieve the intercalation of sodium ions and the removal of potassium ions through the ion exchange method, forming a P2/O3 heterostructure. Combined with the heat treatment step, a sodium-electric layered oxide positive electrode material with high rate performance and cyclic stability is prepared.

Benefits of technology

It realizes the high rate performance and cycle stability of sodium-electric layered oxide positive electrode material, has a high discharge specific capacity, and a stable material structure, which is suitable for fast charging and discharge applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119503887A_ABST
    Figure CN119503887A_ABST
Patent Text Reader

Abstract

According to the preparation method of the heterostructure sodium electric layered oxide positive electrode material, the positive electrode material is of a heterostructure and comprises a P2 and O3 two-phase structure, and a potassium ion layered oxide precursor is subjected to ion exchange and heat treatment to obtain the heterostructure sodium electric layered oxide positive electrode material. According to the preparation method provided by the invention, the sodium electric layered oxide positive electrode material with a P2 / O3 heterostructure can be obtained. In the ion exchange process, sodium ions separated from the sodium-containing molten salt and potassium ions of the potassium ion layered oxide are replaced, under the driving of the chemical potential gradient, intercalation of the sodium ions is accompanied with separation of the potassium ions, the interlayer spacing is gradually reduced under the action of coulomb force, and the P phase is gradually converted into the O phase. According to the invention, the sodium electric layered oxide material with high rate capability and cycling stability is obtained; the material has the fast charging performance, and meanwhile, the long circulation stability is improved. The sodium battery positive electrode material obtained by the method is stable in structure and easy for large-scale application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of battery material synthesis, and in particular relates to a method for preparing a heterogeneous structure sodium-electrode layered oxide positive electrode material with high rate performance and cycle stability. Background Art

[0003] Sodium ion layered oxide Na x TMO2 (TM = transition metal) has the advantages of low cost, high safety performance and high voltage platform, and is widely used in positive electrode materials for sodium ion batteries. According to the stacking method of the sodium layer and the transition metal layer, it is mainly divided into two categories: O3 phase and P2 phase: O3 phase positive electrode material has a higher capacity, but poor cycle stability; P2 phase positive electrode material has good rate performance and cycle performance, but low sodium content and low capacity. The P2 / O3 heterostructure can combine the advantages of the two-phase structure to improve the structural stability while maintaining the capacity. Common methods for preparing P2 / O3 heterostructure sodium-ion layered oxide positive electrode materials include element doping, but the heteroatom doping is uneven and difficult to enter the lattice evenly, resulting in poor product consistency. Therefore, finding an excellent synthesis method is an important problem faced by technicians in this field.

[0004] The Chinese patent application with publication number CN 115986104 A discloses a P2 / O3 mixed phase sodium ion battery positive electrode material and a preparation method thereof. Through a high temperature solid phase method, the Fe and Mn content in the precursor is regulated within a specific Na content range to adjust the P2 / O3 ratio. However, it is difficult to improve the cycle stability while maintaining high energy density. The structural instability of the material itself has not been resolved, and the electrochemical performance has not been greatly improved.

[0005] A Chinese patent application with publication number CN 117594787 A discloses a sodium ion battery positive electrode material with an O3 / P2 mixed-phase structure and a preparation method thereof. The O3 / P2 mixed-phase structure is prepared by regulating the sodium content and doping inert metal elements. However, the introduction of inert elements reduces the proportion of electrochemically active transition metals, and the discharge specific capacity at 1C is low. In addition, heterogeneous atom doping is uneven and difficult to enter the crystal lattice evenly. Summary of the invention

[0006] The technical problem to be solved by the present invention is to overcome the shortcomings of the prior art and provide a method for preparing a heterogeneous structure sodium electrode layered oxide positive electrode material. The obtained heterogeneous structure sodium electrode layered oxide positive electrode material is used to prepare a battery with high rate performance, good cycle stability and high discharge specific capacity.

[0007] The technical solution adopted by the present invention to solve its technical problem is a method for preparing a heterogeneous structure sodium-electrode layered oxide positive electrode material. The positive electrode material is a heterogeneous structure, comprising a two-phase structure of P2 and O3. A potassium ion layered oxide precursor is subjected to ion exchange and heat treatment to obtain the heterogeneous structure sodium-electrode layered oxide positive electrode material.

[0008] Furthermore, the present invention provides a method for preparing a heterogeneous structure sodium-ion layered oxide positive electrode material, wherein the positive electrode material is a heterogeneous structure, comprising a two-phase structure of P2 and O3, and a potassium ion layered oxide K x MO2 is used as a precursor, and potassium and sodium ion exchange is used to achieve structural retention. The potassium ion layered oxide is supplemented with a sodium source for K + / Na + Ion exchange, and finally heat treatment to obtain the finished K + / Na + Ion-exchange heterostructured sodium layered oxide cathode materials y K z MO2.

[0009] The potassium ion layered oxide K x MO2, wherein M is at least one of Fe, Cu, Mn, Ni, and Co. <x≤0.6。

[0010] The heterostructured sodium layered oxide positive electrode material has a molecular formula of Na y K z MO2, wherein M is at least one of Fe, Cu, Mn, Ni, and Co. 0.7 <y≤1,0<z<0.1。

[0011] The method for preparing the heterostructured sodium-electrode layered oxide positive electrode material of the present invention specifically comprises the following steps:

[0012] S1. Preparation of potassium ion layered oxide K x MO2 precursor;

[0013] Potassium ion layered oxide K x The preparation of MO2 precursor is a prior art, including but not limited to high-speed ball milling, solvent thermal, hydrothermal, condensation reflux and / or sintering;

[0014] S2, the obtained potassium ion layered oxide K x The MO2 precursor (i.e., black powder precursor) is mixed with a sodium source and then ion exchange is performed to obtain a bulk material;

[0015] S3, washing the obtained block material (to remove excess molten salt), solid-liquid separation and drying to obtain a powder material, that is, a heterogeneous structure sodium layered oxide positive electrode material Na y Kz MO2. Of which 0.7 <y≤1,0<z<0.1。

[0016] In the present invention, because an excess of sodium salt is added during the reaction process, the bulk material obtained in step S2 is a mixture of a sodium-electrolyte layered oxide positive electrode material and a molten salt. The molten salt in the bulk material in step S2 can be removed by the cleaning step of step S3 to obtain a heterogeneous structure sodium-electrolyte layered oxide positive electrode material.

[0017] Further, in step S1, press K x MO2 stoichiometric weight of the raw materials, in a ball mill for activation, then drying, the resulting dry product sintered to obtain K x MO2.

[0018] Furthermore, in step S1, the high-speed ball milling speed is 300 rpm-600 rpm, and the ball milling time is 3-8 hours. The appropriate ball milling speed can allow the raw materials to be mechanically activated, so that the reaction is more uniform in the subsequent solid phase sintering process.

[0019] Furthermore, in step S1, the sintering is performed in two stages, with program temperature control and a heating rate of 5 to 10°C / min; the temperature of the first stage is 400 to 800°C and the sintering time is 5 to 15 hours; the temperature of the second stage is 700 to 1000°C and the sintering time is 10 to 24 hours. Appropriate sintering time can ensure the synthesis of good layered K x For MO2 precursor, a suitable heating rate can maintain the material structure, and appropriate sintering mechanism and duration can obtain products with better crystallinity.

[0020] Furthermore, in step S2, the ion exchange may be molten salt ion exchange, solid phase ion exchange and / or liquid phase ion exchange.

[0021] Further, in step S2, the temperature of the molten salt ion exchange is 260-380°C and the time is 5-11 hours. Appropriate ion exchange temperature can accelerate the ion exchange rate, and too high ion exchange temperature may cause the molten salt to decompose. Appropriate ion exchange time can increase the proportion of ion exchange.

[0022] Further, in step S2, Na and K in the sodium source x The molar ratio of MO2 precursor is 5 to 15: 1. Appropriate sodium source content can effectively promote the completion of ion exchange, and the appropriate increase in the molar ratio of Na / K can increase the reaction thermodynamics of ion exchange, but too high a molar ratio of Na / K is a waste of resources and is not conducive to environmental protection.

[0023] Further, in step S2, the sodium source is at least one of Na acetate and its hydrate, Na nitrate and its hydrate, Na carbonate, Na hydroxide, and Na chloride. It is preferred to use multiple sodium sources to reduce the melting point of the molten salt and optimize the ion exchange process.

[0024] Further, in step S2, the potassium ion layered oxide K x The MO2 precursor and the sodium source are mixed by grinding. The grinding time is 0.5 to 2 hours. The grinding is carried out under vacuum or protective atmosphere. The protective atmosphere is at least one of nitrogen and inert gas. The inert gas can be argon. The vacuum or protective atmosphere is used to avoid the reaction of the ground and mixed substances with water or carbon dioxide in the air. The appropriate mixing method can effectively mix the precursor and the sodium source evenly, which is convenient for the next step of ion exchange.

[0025] Furthermore, in step S3, the solid-liquid separation is centrifugal separation. The drying is oven drying. The number of centrifugation is 2 to 6 times, the speed is 3000 to 7000 r / min, and the time of each centrifugation is 2 to 15 minutes. The drying temperature is 60 to 120° C., and the drying time is 15 to 30 hours.

[0026] The present invention uses P-phase potassium ion layered oxide as a precursor and adopts K + / Na + By means of ion exchange, sodium ion P2 / O3 heterogeneous materials were synthesized in a directional manner while retaining the layered structure. + / Na + During the exchange process, as potassium ions are removed and sodium ions are embedded, the interlayer spacing gradually decreases under the action of Coulomb force, and the P phase gradually transforms into the O phase, forming a P2 / O3 heterostructure. On the one hand, by adjusting the K / Na molar ratio, the time and temperature of ion exchange, the proportion and rate of ion exchange can be further controlled. On the other hand, some K can be left after ion exchange. + Doping can play a pillar effect at the alkali metal site, stabilizing the lattice structure, supporting the stability of the material structure and preventing structural collapse during subsequent cycles.

[0027] Principle of the invention: The method of the invention first synthesizes K with good layered structure x MO2 precursor, and then through the ion exchange method, this method involves a liquid-solid reaction process, which has the characteristics of fast reaction speed and low temperature. When used in material synthesis, it can be exchanged with the help of the similarity and concentration difference of ions to achieve the purpose of directional control of ion migration and reduce the synthesis conditions.

[0028] Since it is difficult to control the formation of each component phase at the same time, the traditional one-step synthesis process has obvious limitations for the preparation of heterostructure materials. The ion exchange method of the present invention can produce heterostructure materials with excellent physical and chemical properties by controlling the diffusion dynamics of ions in the reactant lattice, accurately adjusting the composition, and forming heterostructures in situ. + / Na + By means of ion exchange, the sodium ion P2 / O3 heterogeneous material is synthesized on the basis of retaining the layered structure. Furthermore, by controlling the ratio and rate of ion exchange, part of the K + Doping can play a pillar effect at the alkali metal site, stabilizing the lattice structure, supporting the stability of the material structure and preventing structural collapse during subsequent cycles.

[0029] Compared with the prior art, the present invention has the following beneficial effects:

[0030] (1) The preparation method provided by the present invention can obtain a sodium-based layered oxide positive electrode material having a P2 / O3 heterostructure. In the process of ion exchange, the sodium ions released from the sodium-containing molten salt are replaced by the potassium ions of the potassium-based layered oxide. Driven by the chemical potential gradient, as the potassium ions are released and the sodium ions are embedded, the interlayer spacing gradually decreases under the action of the Coulomb force, and the P phase gradually transforms into the O phase.

[0031] (2) The present invention obtains a sodium layered oxide material with high rate performance and cycle stability; a portion of K + Under the action of chemical equilibrium, it remains in the alkali metal layer, which can play a supporting role and thus improve the structural stability of the material; the material has fast charging performance while improving long-cycle stability;

[0032] (3) The preparation method provided by the present invention is an ion exchange method. The operation is simple and flexible, and the entire process does not cause pollution. The preparation method provided by the present invention has mild reaction conditions, simple process, high safety, low cost, and easy replication. The sodium positive electrode material obtained by the method of the present invention has a stable structure and is easy to apply on a large scale. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] The accompanying drawings are used to provide a further understanding of the present invention and constitute a part of the specification. Together with the embodiments of the present invention, they are used to explain the present invention and do not constitute a limitation of the present invention. In the accompanying drawings:

[0034] Figure 1 This is the XRD pattern of the positive electrode material obtained in Example 1;

[0035] Figure 2 This is a SEM image of the positive electrode material obtained in Example 1;

[0036] Figure 3 The electrochemical cycle performance diagram of the positive electrode materials obtained in Example 1 and Comparative Example 1;

[0037] Figure 4 The electrochemical rate performance diagram of the positive electrode materials obtained in Example 1 and Comparative Example 1. DETAILED DESCRIPTION

[0038] In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively and meticulously below in conjunction with the accompanying drawings and preferred embodiments of the present invention, but the protection scope of the present invention is not limited to the following specific embodiments.

[0039] Unless otherwise defined, all the professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.

[0040] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.

[0041] The present invention will be further described below in conjunction with specific embodiments and accompanying drawings, but the present invention is not limited to the following embodiments. Unless otherwise defined, all professional terms used hereinafter have the same meaning as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.

[0042] The experimental methods described in the following examples are conventional methods unless otherwise specified; the reagents and materials described are commercially available unless otherwise specified.

[0043] Example 1

[0044] The method for preparing the heterostructured sodium-electrode layered oxide positive electrode material of this embodiment comprises the following steps:

[0045] S1. Press K 0.6 MnO2 stoichiometric number Weigh appropriate amount of Mn2O3 and K2CO3, use anhydrous ethanol as dispersant to perform ball milling activation in a ball mill jar, the speed is 300rpm, and the ball milling time is 5h. Then place it in a blast drying oven for drying, the temperature is 80℃, and the drying time is 12h. The obtained dry product is placed in a muffle furnace, heated to 450℃ at a rate of 5℃ / min and kept for 5h, then heated to 900℃ and sintered for 15h, and then cooled naturally in the furnace to obtain K 0.6 MnO2.

[0046] S2, weigh the mixed molten salt and K 0.6MnO2 precursor, mixed molten salt and K 0.6 The molar ratio of the MnO2 precursor is 10:1. The mass percentage of each component in the mixed molten salt is: 92% NaNO3+6.4% NaCl+1.6% Na2CO3; put it in a mortar and grind it manually for 1 hour in a glove box filled with argon. Place the mixed material in a muffle furnace, heat it to 380℃ at a rate of 5℃ / min, keep it at this temperature for 5 hours, and cool it with the furnace.

[0047] S3, dissolving the block material in a mixed solution of deionized water and anhydrous ethanol, stirring for 20 minutes and then centrifuging, the speed is 3000r / min, each centrifugation time is 7 minutes, and the total centrifugation is 4 times. Then, drying in a blast drying oven, the drying temperature is 80°C, and the drying time is 15 hours, to obtain a powder material, that is, a heterogeneous structure sodium electric layered oxide positive electrode material.

[0048] The material obtained in this example was subjected to ICP test, and the results are shown in Table 1.

[0049] Table 1 ICP-OES test results of materials before and after ion exchange in Example 1

[0050]

[0051] The positive electrode material after ion exchange in this embodiment is assembled into a button battery, and the specific steps are as follows:

[0052] According to the mass ratio (active material: conductive agent: binder = 8:1:1), 0.08g of positive electrode material was weighed, and 0.01g of acetylene black as a conductive agent and 0.01g of polyvinylidene fluoride as a binder were weighed, placed in a mortar and mixed. After mixing evenly, N-methylpyrrolidone was added as a dispersant. After mixing again, the mixture was coated on aluminum foil to make a positive electrode sheet. In a glove box under an inert protective atmosphere, metallic sodium was used as the negative electrode to assemble a CR2032 button battery.

[0053] After the assembled battery was left to stand for 12 hours, the electrochemical performance test was carried out: the positive electrode material obtained after ion exchange had a first-cycle discharge capacity of 168.2 mAh / g at 0.1C (1C = 150 mAh / g). At a discharge rate of 1C, after 100 cycles, it still had a discharge capacity of 96.4 mAh / g, and the capacity retention rate reached 75%.

[0054] Figure 1 is the Na obtained in Example 1 0.7 K 0.01 XRD pattern of MnO2 cathode material, indicating the successful synthesis of P2 / O3 heterostructure.

[0055] Figure 2 is the Na obtained in Example 1 0.7K 0.01 The SEM image of the MnO2 cathode material shows that the material is composed of stacked hexagonal block primary particles. The EDS image shows that the elements of the product after ion exchange are evenly distributed.

[0056] Example 2

[0057] This embodiment includes the following steps:

[0058] S1. Press K 0.6 Mn 0.5 Ni 0.5 O2 stoichiometric number Weigh appropriate amounts of NiO, Mn2O3, and K2CO3, and use anhydrous ethanol as a dispersant to perform ball milling activation in a ball mill jar at a speed of 300rpm for 5 hours. Then place it in a blast drying oven for drying at a temperature of 80°C for 12 hours. Place the obtained dry product in a muffle furnace, heat it to 400°C at a rate of 5°C / min for 5 hours, then heat it to 850°C for sintering for 15 hours, and then cool it naturally in the furnace to obtain K 0.6 Mn 0.5 Ni 0.5 O2.

[0059] S2, weigh the mixed molten salt and K 0.6 Mn 0.5 Ni 0.5 O2 precursor, Na and K in mixed molten salt sodium source 0.6 Mn 0.5 Ni 0.5 The molar ratio of O2 precursor is 15:1, and the mass percentage of each component in the mixed molten salt is 92% NaNO3+6.4% NaCl+1.6% Na2CO3. Put it in a mortar and grind it manually in a glove box filled with argon for 1 hour. The mixed material is placed in a muffle furnace, heated to 360℃ at a rate of 5℃ / min, sintered for 5 hours, and cooled with the furnace.

[0060] S3, dissolving the block material in a mixed solution of deionized water and anhydrous ethanol, stirring for 20 minutes and then centrifuging at a speed of 3000r / min, each centrifugation time of 7 minutes, and centrifuging 4 times in total. Then drying in a blast drying oven at a drying temperature of 80°C and a drying time of 15 hours; obtaining Na y K z Mn 0.5 Ni 0.5 O2.

[0061] The material obtained in this example was subjected to ICP test, and the results are shown in Table 2.

[0062] Table 2 ICP-OES test results of materials before and after ion exchange

[0063]

[0064] The positive electrode material after ion exchange in this embodiment is assembled into a button battery, and the specific steps are as follows:

[0065] According to the mass ratio (active material: conductive agent: binder = 8:1:1), 0.08g of positive electrode material was weighed, and 0.01g of acetylene black as a conductive agent and 0.01g of polyvinylidene fluoride as a binder were weighed, placed in a mortar and mixed. After mixing evenly, N-methylpyrrolidone was added as a dispersant. After mixing again, the mixture was coated on aluminum foil to make a positive electrode sheet. In a glove box under an inert protective atmosphere, metallic sodium was used as the negative electrode to assemble a CR2032 button battery.

[0066] After the assembled battery was left to stand for 12 hours, the electrochemical performance test was carried out: the positive electrode material obtained after ion exchange had a first-cycle discharge capacity of 142.7 mAh / g at 0.1C (1C = 150 mAh / g). At a discharge rate of 1C, after 100 cycles, it still had a discharge capacity of 109.3 mAh / g, and the capacity retention rate reached 76.4%.

[0067] Comparative Example 1

[0068] In this comparative example, a high temperature solid phase method was used to prepare layered oxide Na 0.7 MnO2, the specific steps include:

[0069] S1. Weigh Na2CO3 (5% excess) and MnO2 according to the stoichiometric ratio, and use anhydrous ethanol as solvent to perform low-speed ball milling activation in a ball milling jar at a speed of 300 rpm for 5 hours. Then place in a forced air drying oven for drying at a temperature of 80°C for 12 hours.

[0070] S2. The obtained dried product was placed in a muffle furnace, heated to 450°C at a rate of 5°C / min, kept at this temperature for 5 hours, then heated to 900°C and sintered for 15 hours, and then cooled naturally in the furnace to obtain Na 0.7 MnO2.

[0071] The positive electrode material obtained after heat treatment in this comparative example is assembled into a button battery, and the specific steps are as follows:

[0072] According to the mass ratio (active material: conductive agent: binder = 8:1:1), 0.08g of positive electrode material was weighed, and 0.01g of acetylene black as a conductive agent and 0.01g of polyvinylidene fluoride as a binder were weighed, placed in a mortar and mixed. After mixing evenly, N-methylpyrrolidone was added as a dispersant. After mixing again, the mixture was coated on aluminum foil to make a positive electrode sheet. In a glove box under an inert protective atmosphere, metallic sodium was used as the negative electrode to assemble a CR2032 button battery.

[0073] After the assembled battery was left to stand for 12 hours, the electrochemical performance test was performed. Table 3 shows the Na 0.7 The electrochemical rate performance of MnO2 materials is compared. The data show that the rate performance of Example 1 is significantly improved, and it still has a discharge capacity of 96.6 mAh / g at a high rate of 5C, showing extremely high potential in the field of fast charging and discharging.

[0074] Table 3

[0075]

[0076] Figure 3 The electrochemical cycle performance diagram of the positive electrode materials obtained in Example 1 and Comparative Example 1.

[0077] Figure 4 The electrochemical rate data diagram of the positive electrode materials obtained in Example 1 and Comparative Example 1.

Claims

1. A method for preparing a heterostructured sodium layered oxide positive electrode material, characterized in that: The positive electrode material is a heterogeneous structure, including a two-phase structure of P2 and O3. The potassium ion layered oxide precursor is subjected to ion exchange and heat treatment to obtain the heterogeneous structure sodium electric layered oxide positive electrode material.

2. The method for preparing the heterostructured sodium layered oxide positive electrode material according to claim 1, characterized in that: The positive electrode material is a heterogeneous structure, including a two-phase structure of P2 and O3, with a potassium ion layered oxide K x MO2 is used as a precursor, and potassium and sodium ion exchange is used to achieve structural retention. The potassium ion layered oxide is supplemented with a sodium source for K + / Na + Ion exchange, and finally heat treatment to obtain the finished K + / Na + Ion-exchange heterostructured sodium layered oxide cathode materials y K z MO2.

3. The method for preparing the heterostructured sodium layered oxide positive electrode material according to claim 1 or 2, characterized in that: The potassium layered oxide K x MO2, where M is at least one of Fe, Cu, Mn, Ni, and Co; where 0 < x ≤ 0.6; and / or, the molecular formula of the heterostructure sodium-based layered oxide cathode material is Na y K z MO2, where M is at least one of Fe, Cu, Mn, Ni, and Co; where 0.7 < y ≤ 1, 0 < z < 0.

1.

4. The method for preparing the heterostructured sodium layered oxide positive electrode material according to claim 1 or 2, characterized in that: The specific steps include: S1. Preparation of potassium ion layered oxide K x MO2 precursor; S2, the obtained potassium ion layered oxide K x The MO2 precursor is mixed with a sodium source and then ion exchange is performed to obtain a bulk material; S3, washing the obtained block material, performing solid-liquid separation and drying to obtain a powder material, that is, obtaining a heterogeneous structure sodium layered oxide positive electrode material Na y K z MO2; 0.7 <y≤1,0<z<0.1。 5. The method for preparing the heterostructured sodium layered oxide positive electrode material according to claim 4, characterized in that: In step S1, press K x MO2 stoichiometric weight of the raw materials, in a ball mill for activation, then drying, the resulting dry product sintered to obtain K x MO2.

6. The method for preparing the heterostructured sodium layered oxide positive electrode material according to claim 4, characterized in that: In step S2, the ion exchange is molten salt ion exchange, solid phase ion exchange and / or liquid phase ion exchange.

7. The method for preparing the heterostructured sodium layered oxide positive electrode material according to claim 6, characterized in that: In step S2, the temperature of the molten salt ion exchange is 260-380° C. and the time is 5-11 hours; and / or, In step S2, Na and K in the sodium source x The molar ratio of the MO2 precursor is 5 to 15:

1.

8. The method for preparing the heterostructured sodium layered oxide positive electrode material according to claim 4, characterized in that: In step S2, the sodium source is at least one of Na acetate and its hydrate, Na nitrate and its hydrate, Na carbonate, Na hydroxide, and Na chloride; and / or, In step S2, the potassium ion layered oxide K x The MO2 precursor and the sodium source are mixed by grinding.

9. The method for preparing the heterostructured sodium layered oxide positive electrode material according to claim 8, characterized in that: The grinding time is 0.5 to 2 hours; and / or the grinding is performed under vacuum or protective atmosphere; and / or the protective atmosphere is at least one of nitrogen and inert gas.

10. The method for preparing the heterostructured sodium layered oxide positive electrode material according to claim 4, characterized in that: In step S3, the solid-liquid separation is centrifugal separation; and / or the drying is oven drying; and / or the number of centrifugation is 2 to 6 times, the rotation speed is 3000 to 7000 r / min, and the time of each centrifugation is 2 to 15 min; and / or the drying temperature is 60 to 120° C., and the drying time is 15 to 30 h.

Citation Information

Patent Citations

  • High-performance P2 / O3 mixed-phase sodium-ion battery positive electrode material as well as preparation method and application thereof

    CN115986104A

  • Sodium-ion battery positive electrode material with O3 / P2 mixed-phase structure as well as preparation method and application of sodium-ion battery positive electrode material

    CN117594787A